Assessing the Changes in Bacterial diversity in Rhizosphere and Phyllosphere of Transgenic and Non-transgenic Potato Plant (Plant Tissue Culture and Biotechnology, 2008)
The present communication deals with the study of changes in bacterial community structure in the rhizosphere and phyllosphere under the influence of transgenic and non-transgenic potato plant. The transgenic potato plants used in this experiment synthesize fructan-soluble carbohydrate in the tuber and gives better nutritive value of different biological importance. To assess the changes in bacterial diversity, terminal restriction fragment length polymorphism (T-RFLP)-a fingerprint technique, based on terminal restriction fragment length polymorphism between distinct small-subunit rDNA gene sequence, was used. Three lines of genetically modified (GM) potato (modified from variety-Desiree), one genetically unmodified control (GUM, variety-Desiree) and one traditional potato variety (Linda), were used and sampling was done at full growth stage of potato. Total microbial DNA from rhizosphere and phyllosphere samples was isolated, amplified the 16S rDNA gene for bacterial community with fluoresecence tag primer pair and digested with restriction enzyme HhaI. The digested products were run along with DNA-length standard 100 ROX in an automated genescaner. The T-RFLP analysis resulted in very complex and highly reproducible community fingerprints patterns and showed no clear difference in the bacterial diversity among the rhizosphere of GM, GUM and traditional potato variety. On the other hand, phyllosphere bacterial diversity gave different trend between transgenic and non-transgenic plants. However, the T-RFLP patterns of phyllosphere bacterial community of three GM potato varieties were similar. The same was completely different between GUM and traditional potato varieties.Key words: Assement, Bacterial diversity, Rhizosphere, Transgenic, PotatoDOI = 10.3329/ptcb.v17i1.1125Plant Tissue Cult. & Biotech. 17(1): 87-95, 2007 (June)